(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In this articlecharacteristics of the clinical course of juvenile idiopathic arthritis in childrenThe identity of the correct information is given. Juvenile idiopathic arthritis is a systemic disease of the inflammatory nature of the connective tissue in the joint-visceral type, which is accompanied by damage to the cardiovascular system.